2017
DOI: 10.1162/neco_a_01005
|View full text |Cite
|
Sign up to set email alerts
|

Rat Prefrontal Cortex Inactivations during Decision Making Are Explained by Bistable Attractor Dynamics

Abstract: Two-node attractor networks are flexible models for neural activity during decision making. Depending on the network configuration, these networks can model distinct aspects of decisions including evidence integration, evidence categorization, and decision memory. Here, we use attractor networks to model recent causal perturbations of the frontal orienting fields (FOF) in rat cortex during a perceptual decision-making task (Erlich, Brunton, Duan, Hanks, & Brody, 2015 ). We focus on a striking feature of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…2). These data support a role of the M2-SC pathway in maintaining choice memory 46 . Consistent with this interpretation, comparing perturbation effects in task trials with short versus long delays revealed stronger impairment as delay duration increased ( Fig.…”
Section: Discussionsupporting
confidence: 76%
“…2). These data support a role of the M2-SC pathway in maintaining choice memory 46 . Consistent with this interpretation, comparing perturbation effects in task trials with short versus long delays revealed stronger impairment as delay duration increased ( Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Previous work has emphasized the impact of noise on working memory, arguing this causes a memory to diffuse away from its original state (1,23,24). Our results suggest that underlying attractor dynamics have a significant influence on working memory representations.…”
Section: Main Textmentioning
confidence: 51%
“…Attractor dynamics are thought to reduce the impact of neural noise in long-term memory (20,21) and decision making (22,23) and have been hypothesized to play a similar role in working memory (24)(25)(26). Indeed, our results show attractor dynamics within mnemonic space limit the impact of random diffusion, reducing errors in working memory.…”
Section: Main Textmentioning
confidence: 99%
“…However, considerable controversy remains as to which computations were affected by those disruptions. The effects were largely interpreted in terms of traditional ideal observer models, and thus attributed to perceptual biases (Guo et al, 2018), leaky accumulation (Erlich et al, 2015) or post categorization biases (Piet et al, 2017; Erlich et al, 2015). However, the asymmetric effects on lapses seen in these studies resembled the effects of the reward manipulations in our task, hinting that they may actually arise from action value changes.…”
Section: Resultsmentioning
confidence: 99%